Bicoastal Spontaneous Coronary Artery Dissection: A Therapeutic Dilemma - Ann B. Nguyen Pham; Madushka Y. De Zoysa; Brian B. Ghoshhajra; Nandita S. Scott; Afshan B. Hameed (Thieme Medical Publishers, Inc., 2024)
Due to the potential for severe maternal morbidity and even mortality, pregnancy-associated spontaneous coronary artery dissection (P-SCAD) often presents as a clinical conundrum. While current recommendations encourage coronary interventions when medically indicated even during pregnancy, the hesitation still understandably exists. Meanwhile, given the rarity of the condition, the guidelines for management are still based on expert consensus.